The Efficiency of Employee Performance in Enhancing the Service of the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency of Biak Numfor Regency on Providing Land Certificates - Krismiyati Krismiyati (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The efficiency of services has been established as the foundation for imaging for persons in need of services. The purpose of this study was to determine the efficiency of employees' performance in surprising the service of issuing land certificates at the Ministry of Affairs and Spatial Planning / National Land Agency in Biak Numfor Regency, based on factors that could affect the quality of Regional Taxpayer Identification Number services, as well as their inhibitory factors. The findings of this study reveal that employee performance has not been effective in increasing the service of issuing land certificates in this office, as evidenced by a shortage of human resources and a low degree of employee knowledge of work discipline. Additionally, the prostemy's means are kept to a minimum at the office, which is geographically located near the communities. As a result, different repair operations must be carried out by the Ministry of Affairs and Spatial Planning/National Land Agency's headquarters, as well as by heads and staff at the Ministry of Affairs and Spatial Planning/National Land Agency of Biak Numfor Regency office. Additionally, the findings of this study support the need for additional research to demonstrate efforts to supervise and evaluate human resources, service management, and infrastructure facilities in order to increase employee efficiency in generating land certificates quickly, evenly, and effectively, which impacts employee satisfaction and equitable service at The Ministry of Land. The solution to the constraints encountered during the efficiency process at the Supiori Regency Bapenda office is as follows: (a) increase the number of employees and improve employee education with a high school diploma or equivalent to a Bachelor's degree (S1) to increase competence; (b) prioritize fast service by increasing network connection access to the server; and (c) service procurement.